2018
DOI: 10.1186/s12876-018-0780-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori infection and bone mineral density: a retrospective cross-sectional study

Abstract: BackgroundHelicobacter pylori (H. pylori) infection can induce individual inflammatory and immune reactions which associated with extra-digestive disorders. Our aim is to investigate the association between H. pylori infection and bone mineral density.MethodsThis retrospective cross-sectional study was performed by using the data from the health examination database in a medical center of southern Taiwan in 2013. We investigated the relationship between sex, age, body mass index (BMI), waist circumstance, lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The second report [ 125 ], based on analysis of 50,002 patients with PUD and equal number of controls matched by age, gender, past medical history, income and residence region, found increased risk of OP in PUD regardless of gender (adjusted HR 1.36, 95% CI 1.33–1.40). In contrast, a retrospective cross-sectional study from China ( n = 867, with PUD 351 patient) reported that PUD was significantly associated with decreased BMD only in univariate analysis (OR 1.37, 95% CI 1.03–1.82) [ 117 ]. Lastly, in a cohort of patients operated for PUD between 1956 and 1985 (pre-HPI era) and followed for 30 years, the risk of OF was significantly (and independently of surgical procedure type) increased showing a standardized incidence ratio of 2.5 for the proximal femur, 4.7 for vertebra and 2.2 for the distal forearm [ 126 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The second report [ 125 ], based on analysis of 50,002 patients with PUD and equal number of controls matched by age, gender, past medical history, income and residence region, found increased risk of OP in PUD regardless of gender (adjusted HR 1.36, 95% CI 1.33–1.40). In contrast, a retrospective cross-sectional study from China ( n = 867, with PUD 351 patient) reported that PUD was significantly associated with decreased BMD only in univariate analysis (OR 1.37, 95% CI 1.03–1.82) [ 117 ]. Lastly, in a cohort of patients operated for PUD between 1956 and 1985 (pre-HPI era) and followed for 30 years, the risk of OF was significantly (and independently of surgical procedure type) increased showing a standardized incidence ratio of 2.5 for the proximal femur, 4.7 for vertebra and 2.2 for the distal forearm [ 126 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…Low serum B12 levels affect DNA synthesis, an important factor for bone remodeling. Vitamin B12 (and other B vitamins—B2, B6 and folate—linked to homocysteine metabolism) is regarded an essential factor for bone health [ 117 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ]. Vitamin B12 deficiency was reported to have an increased fracture risk: 1.7- to [ 162 ] 1.9-fold [ 163 ] for hip fracture, 1.8-fold for vertebral fracture [ 163 ] and 2.9-fold for distal forearm fracture [ 163 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies hold the view that obesity is related to osteoporosis [29]. It is generally believed that obesity may be a protective factor against bone loss and osteoporosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies on the relationship between H. pylori infection and osteoporosis have yielded heterogeneous findings so far, whereby positive 15,16 and negligible associations 17,18 have been reported. A recent meta-analysis showed that H. pylori infection was associated with osteoporosis [odds ratio (95% confidence interval): 1.39 (1.13--1.71)] but not significantly with BMD at the hip, lumbar and femur.…”
Section: Discussionmentioning
confidence: 99%